2013
DOI: 10.1371/journal.pone.0068466
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Grazing History, Cattle Removal and Time since Rain Drive Divergent Short-Term Responses by Desert Biota

Abstract: Arid grasslands are used worldwide for grazing by domestic livestock, generating debate about how this pastoral enterprise may influence native desert biota. One approach to resolving this question is to experimentally reduce livestock numbers and measure the effects. However, a key challenge in doing this is that historical grazing impacts are likely to be cumulative and may therefore confound comparisons of the short-term responses of desert biota to changes in stocking levels. Arid areas are also subject to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
30
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 64 publications
4
30
1
2
Order By: Relevance
“…We expected that dragon lizards (agamids) would increase and skinks (scincids) decrease in abundance based on previous work in the region (Read 2002;Read and Cunningham 2010). Limited information exists for mammalian species and taxa that occur in the area, but we postulated that native rodent and dasyurid species abundance would most likely decrease at more intenselygrazed sites (Read and Cunningham 2010;Frank et al 2013). We expected that the exotic Mus musculus would increase in abundance with increasing grazing intensity owing to its generalist life-history and ability to colonise post-disturbance environments (Robinson et al 2000).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…We expected that dragon lizards (agamids) would increase and skinks (scincids) decrease in abundance based on previous work in the region (Read 2002;Read and Cunningham 2010). Limited information exists for mammalian species and taxa that occur in the area, but we postulated that native rodent and dasyurid species abundance would most likely decrease at more intenselygrazed sites (Read and Cunningham 2010;Frank et al 2013). We expected that the exotic Mus musculus would increase in abundance with increasing grazing intensity owing to its generalist life-history and ability to colonise post-disturbance environments (Robinson et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, arid and semi-arid rangelands are dominated by livestock grazing systems that encompass a greater area than any other land use (Frank et al 2013). It has been suggested that the ecological consequences of grazing, particularly in north-western America, are substantial, and include changes in the composition of communities and in ecosystem structure, and disturbance to ecosystem function (Fleischner 1994).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations